2020
DOI: 10.1017/s1368980020001949
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of trans-fatty acid content in a sample of foods from the Slovenian food supply using a sales-weighting approach

Abstract: Objective: Consumption of trans-fatty acids (TFA) is a well-established risk factor for CVD morbidity and mortality. Our objective was to investigate TFA levels in Slovenian food supply. Design: Cross-sectional study. Setting: Selected foods (n 282) were purchased in Slovenia (2016), and the TFA content was determined. The sample included pre-packed foods with/without declared partially hydrogenated vegetable oils (PHO), as well as non-pre-packed foods. A sales-weightin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Previous studies on iTFA content in our region have identified biscuits as a critical food category (6,15,(23)(24)(25). High amounts of more than 2% iTFA of total fat was observed in many products of prepacked biscuits, cakes and wafers with at least 15 g fat/100 g of product and PHO or a similar term on list of ingredients in Serbian (n = 35) and Slovenian markets (n = 18) in 2012 (15).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous studies on iTFA content in our region have identified biscuits as a critical food category (6,15,(23)(24)(25). High amounts of more than 2% iTFA of total fat was observed in many products of prepacked biscuits, cakes and wafers with at least 15 g fat/100 g of product and PHO or a similar term on list of ingredients in Serbian (n = 35) and Slovenian markets (n = 18) in 2012 (15).…”
Section: Discussionmentioning
confidence: 78%
“…When we compared our data with regard to the country of product production (EU countries with those from non-EU countries), we found high TFA content in total fat in 37.5% products from EU compared to 75% from non-EU countries, confirming variability in TFA between countries. In 2016, Kušar et al (25) determined iTFA content in 282 selected food purchased in Slovenia, including 39 biscuits. The authors reported that considerable variability was observed in TFA content in biscuits, ranging up to 4.88 g/100 g of food within the PHO-containing samples.…”
Section: Discussionmentioning
confidence: 99%
“… List only include studies where Slovenian branded food databases were exploited directly. Food monitoring studies datasets were used for several other studies, for example, to support in the sampling of foods in the food supply for assessment of the content of trans fatty acids in foods ( 64 , 65 ), for assessment of salt iodization ( 66 ), for assessment of dietary intakes ( 67 71 ), food marketing ( 25 , 72 74 ) and offers in vending machines ( 75 , 76 ). Studies exploiting additional Slovenian branded foods composition datasets ( 44 , 66 , 77 79 ) are also not included .…”
Section: The Exploitation Of Use Of Branded Foods Database In Nutrition Researchmentioning
confidence: 99%
“…In such cases, branded foods datasets can be used to support the selection of foods for laboratory analyses. For example, Kušar et al ( 64 ) and Mencin et al ( 65 ) used the 2017 dataset to select branded foods for determining the number of trans fatty acids (TFA) analytically. Studies have identified specific food categories with higher content of TFAs, supporting the Slovenian government in implementing a regulatory ban on such foods ( 102 ).…”
Section: The Exploitation Of Use Of Branded Foods Database In Nutrition Researchmentioning
confidence: 99%
“…The USA has completely banned the use of PHVO in pre-packaged foods in 2018 (13) . In 2019, the European Commission imposed a trans-fat limit (for industrially produced trans-fat only) of ≤ 2 % of total fat (% total fat ) to in pre-packaged food, with full enforcement starting in 2021 (14,15) . Many countries around the world, however, still do not have plans in place to eliminate industrial trans-fat from the food supplyparticularly many Asian and African countries (16) .…”
mentioning
confidence: 99%